Relationships between Providers and Users of Market Research: The Dynamics of Trust within and between Organizations - Moorman, Christine; Zaltman, Gerald; Deshpande, Rohit (Journal of Marketing Research, 1992)
The authors investigate the role of trust between knowledge users and knowledge providers. The kind of knowledge of special concern is formal market research. Users include marketing and nonmarketing managers; providers include marketing researchers within a user's own firm and those external to the firm. A theory of the relationships centering on personal trust is developed to examine (1) how users’ trust in researchers influences various relationship processes and the use of market research and (2) how the relationships vary when examined across dyads. The relationships were tested in a sample of 779 users and providers of market research information. Results indicate that trust and perceived quality of interaction contribute most significantly to research utilization, with trust having indirect effects through other relationship processes, as opposed to important direct effects on research utilization. Deeper levels of exchange, including researcher involvement in the research process and user commitment to the research relationship, however, have little effect on research use. Finally, the relationships in the model show few differences depending on whether the producer and user share marketing or research orientations. Interorganizational dyads, however, generally exhibit stronger model relationships than intraorganizational dyads.